Beyond Exposure: Advertising and Celebrity Endorsers Influence Brand Awareness and Purchase Decisions - Maharini Rahsilaputeri; Lela Nurlaela Wati; Momon Momon; Zulfa Tazkia Anbiya (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study analyzes the influence of advertising and celebrity endorsers on purchasing decisions through brand awareness. Using a quantitative approach with 260 respondents and SEM-PLS for data analysis. The results show that advertising increases consumer awareness of the brand and encourages them to purchase Marina hand & body lotion. Celebrity endorsers have a positive effect on brand awareness but do not directly influence purchasing decisions. However, brand awareness mediates the influence of celebrity endorsers on purchasing decisions. Celebrity endorsers do not have a direct impact on purchasing decisions, but have a positive impact through brand awareness. These findings support the AIDA model, source credibility theory, and the importance of brand awareness in promotions. Companies should create advertisements that attract attention, spark interest, foster desire, and drive action, emphasizing brand identity for easy recognition. Advertising evaluations should focus on boosting brand awareness, not just sales. When using celebrity endorsers, companies should choose trustworthy, expert, and attractive figures who reinforce brand memory. The novelty of this research lies in positioning brand awareness as the main mediator between advertisements and celebrity endorsers on purchasing decisions within the hand & body lotion context with second order confirmatory approach